PENDIDIKAN SEBAGAI MEDIA INTEGRASI AGAMA DAN SAINS DALAM ERA REVOLUSI INDUSTRI 4.0 - Irwan Fathurrochman; Edison Edison (Yayasan Literasi Kita Indonesia, 2020)
Education is not just merely transferring knowledge, but alsotransforming the values of truth, justice, honesty, humanity, and divinity into thehearts of students. Islam is a religion that is in accordance with human nature, itsshari'a is not only encouraging people to learn science and technology, then tobuild civilization, even to organize their people to survive and save both in theworld and in the hereafter. Religion and science have no opposition, are integral,cannot be separated from one another. Integration of religion and science is notjust an epistemological study, but it should be implemented axiologically in thelearning process at every level of education. Facing the globalization era that weare familiar with in the era of industrial revolution 4.0, the integration of religionand science is a necessity.